A Study on Polymeric Reagent Uses in Organic Synthesis: Applications and Mechanisms of Polymeric Reagents in Organic Synthesis (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The key benefits of the use of polymeric carriers in organic synthesis are solubilization, immobilization and the development of unique microenvironmental and steric results. Recent development has been explored in the usage of polymer reagents in organic synthesis.For high-efficiency acylation (e.g. peptide synthesis), for halogenation, for oxidation and reduction in the Wittig reaction, condensation and other reactions, polymeric transfer agents were used. This method typically requires an abundance of polymeric reagent such that a sufficient product yield is reached in solution. Side compounds stay stuck to the polymer in several of these reactions, enabling chemical purification.In his peptide synthesis, Merrifield originated organic synthesis of polymer carriers. The 'hoop lane' synthesis, selective mono reactions of bifunctional compounds, and oligosaccharide synthesis are recent examples of synthesis using the same method. An abundance of soluble reagent is typically used in this reaction form.Reactive agents in polymer transporters is used in cycling reactions, ester enolate reactions, mixed ester condensations, coordinated unsaturated catalyst preparations, and enzyme subunit isolation. The effectiveness of these reactions depends on the chain length and concentration of the molecules connected and polymer interconnection, reaction temperature and time.